Assessment of personnel risks at adoption of administrative decisions - Tsvetkova, I. (Lviv Polytechnic National University, 2014)
In article the technique of an assessment of personnel risks is developed at a choice of optimum version of the administrative decision. The analysis of alternatives in the course of decision-making assumes serial consideration of all candidates solution with determination of advantages and shortcomings of each option by all possible criteria, including on a factor of personnel risks. Following the results of an assessment the card of risks is formed, and the assessment of an acceptability of lternative is defined as average weighed by each stage of realization of alternative where as weight information evaluation test is accepted.
Keywords: personnel risks; alternatives of the decision; risks map; rating scale